![Raus](https://sproshu.net/uploads/ava/1/ava4916.jpg)
Raus
6 год назад
2ctg(x-1)+3tg(x-1) = 5
ОТВЕТЫ
![Ефремович](https://sproshu.net/uploads/ava/4/ava6822.jpg)
Ефремович
Jul 1, 2019
Решение
2ctg(x-1)+3tg(x-1)=5
2*(1/tg(x-1)+3tg(x-1)=5 умножим на tg(x-1) ≠ 0
3tg²(x-1) - 5tg(x-1) + 2 = 0
tg(x-1) = t
3t² - 5t + 2 = 0
D = 25 - 4*3*2 = 1
t₁ = (5 - 1)/6
t₁ = 2/3
t₂ = (5 + 1)/6
t₂ = 1
1) tg(x-1) = 2/3
x - 1 = arctg(2/3) + πk, k ∈ Z
x₁ = arctg(2/3) + 1 + πk, k ∈ Z
2) tg(x-1) = 1
x-1 = π/4 + πn, n ∈ Z
x₂ = π/4 + 1 + πn, n ∈ Z
Ответ: x₁ = arctg(2/3) + 1 + πk, k ∈ Z ; x₂ = π/4 + 1 + πn, n ∈ Z
2ctg(x-1)+3tg(x-1)=5
2*(1/tg(x-1)+3tg(x-1)=5 умножим на tg(x-1) ≠ 0
3tg²(x-1) - 5tg(x-1) + 2 = 0
tg(x-1) = t
3t² - 5t + 2 = 0
D = 25 - 4*3*2 = 1
t₁ = (5 - 1)/6
t₁ = 2/3
t₂ = (5 + 1)/6
t₂ = 1
1) tg(x-1) = 2/3
x - 1 = arctg(2/3) + πk, k ∈ Z
x₁ = arctg(2/3) + 1 + πk, k ∈ Z
2) tg(x-1) = 1
x-1 = π/4 + πn, n ∈ Z
x₂ = π/4 + 1 + πn, n ∈ Z
Ответ: x₁ = arctg(2/3) + 1 + πk, k ∈ Z ; x₂ = π/4 + 1 + πn, n ∈ Z
147
Смежные вопросы: